Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.222
|View full text |Cite
|
Sign up to set email alerts
|

Effective Work Practices for FLOSS Development: A Model and Propositions

Abstract: We review the literature on Free/Libre Open Source Software (FLOSS) development and on software development, distributed work and teams more generally to develop a theoretical model to explain the performance of FLOSS teams. The proposed model is based on Hackman's [1] model of effectiveness of work teams, with coordination theory [2] and collective mind [3] to extend Hackman's model by elaborating team practices relevant to effectiveness in software development. We propose a set of propositions to guide furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…However, open source research is often viewed as its own track and is not frequently associated with the study of virtual communities. This may be due to the fact that much of this open source research addresses software/ technical/work process issues (Crowston et al 2005) and not social/community issues.…”
Section: Virtual Communities In Oss Projectsmentioning
confidence: 99%
“…However, open source research is often viewed as its own track and is not frequently associated with the study of virtual communities. This may be due to the fact that much of this open source research addresses software/ technical/work process issues (Crowston et al 2005) and not social/community issues.…”
Section: Virtual Communities In Oss Projectsmentioning
confidence: 99%
“…However, free software is also an ideology and a lifestyle [65,68]. FLOSS projects are usually described by concentric circles [19]. The most inner circle represents coders who have direct write access to the official code.…”
Section: Introductionmentioning
confidence: 99%
“…Their adherence to the FLOSSD ideology enhances communication and trust, amplifying team effectiveness (Stewart and Gosain 2006). Crowston et al (2005) found that team effectiveness was dominated by team composition and organizational context rather than tools or other technical factors. Rather than traditional forms of vertical and horizontal coordination (above; Nidumolu 1995), FLOSSD projects are coordinated using "informalisms" -boundary objects describing or prescribing aspects of the project including discussion forum threads, project wikis and to-do lists -which replace formalisms including requirements specifications and system documentation (Scacchi 2007).…”
Section: The Scope Of the Design Agentmentioning
confidence: 99%